Дослідження особливостей формування прибутку організації в сучасних умовах господарювання - Гавран, В. Я.; Середницька, Х. Т. (Видавництво Львівської політехніки, 2016)
Розглянуто теоретичні засади прибутку, проаналізовано сутність та значення результативних показників діяльності. Здійснено розрахунки на основі статистичних даних підприємств та проведено дослідження впливу головних факторів на результативні показники діяльності організацій, виділено їхні основні проблеми та заходи підвищення ефективності господарювання. The article investigates the modern period of economic activity of organizations under significantly increasing cost of resources conditions, losing of markets, currency devaluation, reducing profitability and losses levels of many companies. The authors analysed the scientific investigations of profit nature, evaluation parameters and ways to improve them. The main objectives of the study are formed and they require diagnosing problems of forming performance indicators and finding ways for their improvement. The calculations of the value and dynamics of indicators based on statistical data of enterprises are done. The impact of the key factors on the companies’ performance is studied as well. The authors highlight their main problems and measures to increase efficiency.
Researching peculiarities of forming company’s profit in the current economic conditions
Keywords: прибуток; результативні показники; факторний аналіз; обсяг реалізації; цінові показники; собівартість; profit; performance indicators; factor analysis; sales; price indicators; cost